Cyclodextrin-modified micellar electrokinetic chromatography for the enantioseparation of imidazole and vinpocetine drugs - Abd. Wahib, Siti Munirah (2012)
In the present work, cyclodextrin-modified micellar electrokinetic chromatography (CD-MEKC) method was developed and applied for enantioseparation of three imidazole drugs and vinpocetine. The three imidazole drugs namely tioconazole, isoconazole and fenticonazole were simultaneously separated for the first time by MEKC technique using dual cyclodextrin (CD) approach. A combination of two neutral CDs; 2-hydroxypropyl--CD (HP--CD) and heptakis (2,6-di-O-methyl)--CD (DM--CD) (35 mM: 10 mM) in background electrolyte (BGE) containing 35 mM phosphate buffer (pH 7.0), 50 mM sodium dodecyl sulfate (SDS) and 15% (v/v) acetonitrile at 27 kV and 30oC gave the best separation of six stereoisomers of imidazole drugs with resolutions, Rs 1.90-27.22 and peak efficiencies, N > 180 000 in less than 15 min. The samples were injected electrokinetically at 3 kV for 3 s and detection was carried out at 200 nm. The method was linear over the concentration range of 25-200 mg/L (r2 > 0.998) and the detection limits (S/N = 3) of the three imidazole drugs were found to be 2.7-7.7 mg/L. The CD-MEKC method was successfully applied to the determination of the three imidazole drugs in spiked human urine to give mean recoveries ranging from 72.3 to 107.5% (RSD < 6%, n = 3). The method was also applied to the analysis of commercial cream formulation of tioconazole and isoconazole. Good mean recoveries were obtained, ranging from 93.6-100% (RSD < 7%, n = 3). The best chiral separation of vinpocetine that gave four resolved peaks was achieved using 40 mM HP--CD in 50 mM phosphate buffer (pH 7.0) consisting of 40 mM SDS and 10% v/v acetonitrile at a separation temperature of 25oC and separation voltage 25 kV. Samples were injected electrokinetically at 5 kV for 7 s. Vinpocetine detection was accomplished using diode array detector at 200 nm. The complete vinpocetine separation was achieved in less than 15 min with peak resolution, Rs 1.40-5.80.